Perbandingan Mocaf Dengan Tepung Kacang Merah (Phaseolus vulgaris) Terhadap Karakteristik Tortilla Bebas Gluten - Andrea Rivanya Prameswary; Anak Agung Istri Sri Wiadnyani; I Putu Suparthana (Itepa : Jurnal Ilmu dan Teknologi Pangan, 2026)
Tortilla is a type of flatbread commonly made from wheat flour. However, the gluten content in wheat poses health risks for individuals with celiac disease. Therefore, innovation in tortillas products with characteristics similar to wheat-based tortillas is needed. This study aimed to determine the effect of varying ratios of modified cassava flour (mocaf) and red bean flour on the chemical, physical, and sensory characteristics of gluten-free tortillas, as well as to identify the optimal formulation. The experimental design used a Completely Randomized Design (CRD) with six treatment ratios of mocaf to red bean flour (100:0, 90:10, 80:20, 70:30, 60:40, 50:50), each replicated three times. Observed parameters included moisture, protein, fiber, ash, fat, carbohydrates, antioxidant activity, texture profile (tensile strength, elongation, and hardness), and sensory evaluations (color, aroma, taste, texture, scoring, and overall acceptance). Data were analyzed using ANOVA and further tested with Duncan’s Multiple Range Test (DMRT) at a significance level of α = 0.05. The results showed that the flour ratio significantly affected all observed parameters. The best formulation was 70% mocaf:30% red bean flour, with a moisture content of 31,48%, protein 4,49%, fiber 5,02%, ash 2,99%, fat 6,95%, antioxidant activity 18,98%, tensile strength 0,06 MPa, elongation 35,66%, hardness 14,69 N. The sensory evaluation showed scores of slightly liked for color, taste, aroma, texture, and overall acceptance, while softness intensity was rated as slightly hard. Compared to wheat-based tortillas, the 70% mocaf:30% red bean flour formulation showed advantages in moisture, fiber, protein, ash, and antioxidant content.